Association of fetal growth trajectory with mitochondrial DNA copy number in the cord blood of newborns: evidence from a birth cohort - Chen, Kai; Li, Junwei; Xu, Luli; Fan, Xiaoxuan; Cao, Zhongqiang; Song, Lulu; Wang, Youjie; Xiong, Chao; Zhou, Aifen (Frontiers in Pediatrics, 2025)
ObjectiveMitochondrial DNA copy number (mtDNAcn), an indicator of mitochondrial damage and dysfunction, is widely used in research related to growth and metabolic health. While fetal intrauterine growth has been reported to impact further metabolic health, there is limited evidence regarding the relationship between fetal growth patterns and newborn mtDNAcn, especially in infants with normal birth weights, where varying fetal growth patterns can occur despite having the same birth weight. Therefore, this study aimed to examine the association between fetal growth trajectory and neonatal mtDNAcn among normal birth weight infants.MethodsA total of 556 mother–infant pairs from a birth cohort in Wuhan, China, were included in the study. Ultrasound measurements (biparietal diameter, head circumference, abdominal circumference, and femoral length) were taken at 16, 24, 30, and 37 weeks of pregnancy and converted to Z-scores per WHO standards, and the fetal growth trajectory was fitted by the group-based multi-trajectory model. Cord blood was collected at birth, and mtDNAcn in cord blood was quantified via real-time fluorescent quantitative PCR. A generalized linear model was used to explore the associations of fetal growth pattern or birth weight with neonatal mtDNAcn.ResultsThree distinct patterns of fetal growth trajectory were identified, namely, “consistently low” (n = 144, 25.9%), “moderate” (n = 304, 54.7%), and “high-falling” (n = 108, 19.4%). Compared with the “moderate” intrauterine growth pattern, the “consistently low” intrauterine growth pattern was associated with lower neonatal mtDNAcn among male newborns, with a reduction of 22.55% (95% CI: −39.19%, −1.37%; p = 0.039). No significant association was detected between the intrauterine growth pattern and mtDNAcn among girls.ConclusionsOur findings indicate that different intrauterine growth patterns are present in fetuses with normal birth weights. In male infants, the “consistently low” intrauterine trajectory pattern was associated with decreased neonatal mtDNAcn. The effective detection of and intervention in fetal intrauterine growth patterns may help prevent metabolic health events early in life.